A Study on Level of Teaching Among Unaided College Teachers with Reference to Coimbatore City - S Renugadevi; P Ramakrishnan (Journal of Advanced Research in Public Policy and Administration, 2021)
This study was conducted to explore the Attitude of College teachers towards digital based teaching. The sample of this study included 60 Unaided College teachers. The self developed questionnaire was used by the investigator to access Attitude of unaided College teachers towards digital based teaching. The objectives of the study were to study the unaided College teachers. To study the significant difference in the attitude of unaided College teachers. The results supported that there is no significant difference in the attitude of lectures towards digital based teaching they beliefs that digital based learning is an important tool for enhancing the teaching process in a classroom situation. It made an enormous contribution to improving education. The aided students used the internet most frequently for entertainment (57.0%), while as the unaided students used it for education (57.4%). Both groups of students used the internet very frequently to chat with friends, for social networking, email, and to obtain general information. For the aided students, the biggest barriers to using the internet were a lack of time (42.0%) and cost of using (41.1%) and for unaided students were a lack of time (65.7%) and lack of internet at home (19.9%). Implications of the results are discussed. How to cite this article: S Renugadevi, P Ramakrishnan. A Study Level of Teaching with Unaided College Teachers with Reference to Coimbatore City. J Adv Res Pub Poli Admn 2020; 2(2): 1-4.